(untitled) (Studia Prawnicze / The Legal Studies, 1983)
The aim of the article is to present the process of unification of law within the CMEA and ECM and to establish the influence of the process on exchange of goods between the East and West. The author tries to point out that the process of unification of commercial law, even if it occurs at a regional level, facilitates transacting business between socialist enterprises and West European firms. The author favourably evaluates uniform regulation of law on foreign trade within the CMEA in a form of general terms of delivery and shows their practical influence on contracts concluded by socialist enterprises with West European firms. He also presents the influence of uniform Hague law in the field of foreign trade on special legislation binding in some socialist states.